Teacher Pjok's Perception in Online Learning During the Covid-19 Pandemic in Middle Schools in Central Bengkulu Regency - Didit Domi Saputra; Citra Dewi; Mariska Febrianti (Sinar Sport Journal, 2021)
This study aims to determine and analyze the perceptions of PJOK teachers in online learning during the Covid-19 pandemic in junior high schools in Central Bengkulu Regency, Bengkulu Province. The research method used is descriptive quantitative method. This method is a research method used to examine the population and sample. The statistical analysis of the data is quantitative in nature. This research uses a survey method. while the data collection using an online questionnaire. Sampling technique is a sampling technique. Sampling techniques are basically grouped into two, namely probability sampling and non-probability sampling as many as 30 people. From the description of the research results, it can be seen that the Perceptions of PJOK Teachers in Central Bengkulu Regency based on Functional Factors Strongly Agree 6% (1 Teacher), Agree 24% (4 Teachers), Disagree 71% (12 People), Strongly Disagree 0% ( 0 Master). Structural Factors Strongly Agree 100% (17 Teachers), Agree 0% (0 Teachers), Disagree 0% (0 Teachers), Strongly Disagree 0% (0 Teachers).